Proton-air interactions at ultra-high energies in muon-depleted air showers with different depths - L. Cazon; R. Conceição; M.A. Martins; F. Riehn (Physics Letters B, 2024)
The hardness of the energy spectrum of neutral pions produced in proton-air interactions at ultra-high energies, above 1018 eV, is constrained by the steepness of the shower-to-shower distribution of the number of muons in muon-depleted extensive air showers.In this work, we find that this steepness, quantified by the parameter Λμ, evolves with the depth of the shower maximum, Xmax, assuming a universal value for shallow showers and an enhanced dependence on the high-energy hadronic interaction model for deep showers. We show that Xmax probes the so-called hadronic activity of the first proton-air interaction, thus allowing direct access to the energy spectrum of neutral pions in different regions of its kinematic phase space.We verify that the unbiased measurement of Λμ is possible for realistic mass composition expectations. Finally, we infer that the statistical precision in Λμ required to distinguish between hadronic interaction models can be achieved in current extensive air shower detectors, given their resolution and exposure.